Unusual structures and unknown roles of FeS clusters in metalloenzymes seen from a resonance Raman spectroscopic perspective - Caserta, Giorgio (2022)
Funding Information: This work was financially supported by: Project LISBOA-01-0145-FEDER-007660 (Microbiologia Molecular, Estrutural e Celular) funded by FEDER funds through COMPETE2020 - Programa Operacional Competitividade e Internacionaliza??o (POCI) and by national funds through FCT - Funda?a?o para a Cie?ncia e a Tecnologia; by the European Union's Horizon 2020 research and innovation programme, TIMB3, GA No 810856. ST acknowledges PTDC/BTM-SAL/29507/2017 and CMS acknowledges PTDC/BIA-BFS/31026/2017 project and CB acknowledges 2020.05017.BD fellowship granted by FCT. GC, IZ and PH thank the Einstein Foundation Berlin (grant number EVF-2016-277) for funding. This work was also supported through the cluster of excellence ?UniSysCat? funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany?s Excellence Strategy-EXC2008/1-390540038 and the SPP 1927 ?Iron sulfur for Life? - ZE 510/2-2 (IZ). Funding Information: This work was financially supported by: Project LISBOA-01-0145-FEDER-007660 (Microbiologia Molecular, Estrutural e Celular) funded by FEDER funds through COMPETE2020 - Programa Operacional Competitividade e Internacionalização (POCI) and by national funds through FCT - Fundação para a Ciência e a Tecnologia; by the European Union’s Horizon 2020 research and innovation programme, TIMB 3 , GA No 810856. ST acknowledges PTDC/BTM-SAL/29507/2017 and CMS acknowledges PTDC/BIA-BFS/31026/2017 project and CB acknowledges 2020.05017.BD fellowship granted by FCT. GC, IZ and PH thank the Einstein Foundation Berlin (grant number EVF-2016-277) for funding. This work was also supported through the cluster of excellence “UniSysCat“ funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germanýs Excellence Strategy-EXC2008/1-390540038 and the SPP 1927 ”Iron sulfur for Life” - ZE 510/2-2 (IZ). Publisher Copyright: © 2021 The Authors